2014
DOI: 10.1371/journal.pone.0091247
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Home Environment Interventions on the Risk of Influenza-Associated ARI in Andean Children: Observations from a Prospective Household-Based Cohort Study

Abstract: BackgroundThe Respiratory Infections in Andean Peruvian Children (RESPIRA-PERU) study enrolled children who participated in a community-cluster randomized trial of improved stoves, solar water disinfection, and kitchen sinks (IHIP trial) and children from additional Andean households. We quantified the burden of influenza-associated acute respiratory illness (ARI) in this household-based cohort.MethodsFrom May 2009 to September 2011, we conducted active weekly ARI surveillance in 892 children age <3 years, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Similarly, we did not include altitude in our estimations. Previous studies conducted in the same population have reported higher rates of influenza infection occurring between 2,322– 2,641 meters above sea level compared with higher altitudes 9 . Similarly, higher rates of RSV were noted between 2,626– 2,865 meters above sea level compared with higher altitudes 30 .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Similarly, we did not include altitude in our estimations. Previous studies conducted in the same population have reported higher rates of influenza infection occurring between 2,322– 2,641 meters above sea level compared with higher altitudes 9 . Similarly, higher rates of RSV were noted between 2,626– 2,865 meters above sea level compared with higher altitudes 30 .…”
Section: Discussionmentioning
confidence: 67%
“…Few studies have characterized the burden of viral ARI among children living in high altitude settings, such as the Peruvian Andes. Our previous studies conducted in this region 6,8,9 reported an overall ARI incidence rate of 62 [95% CI: 59–65] per 100 child-years 8 . The incidence rate of influenza ARI was 37 per 100 child-years, which is as high or higher than rates from other low and middle income counties 9 , such as Bangladesh and Vietnam 7,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Recent studies using molecular detection have suggested that influenza C is more frequent in children than previously recognized. 24,26,[28][29][30][31] Clinical Symptoms…”
Section: Influenza C Backgroundmentioning
confidence: 99%
“…31 Influenza C has been associated with fewer febrile days and less health care utilization than influenza A or B, suggesting a milder pathogen. 29 Like other influenza types, influenza C has been associated with encephalopathy. 32…”
Section: Influenza C Backgroundmentioning
confidence: 99%